2008
DOI: 10.3130/jaabe.7.139
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction Potential of Energy Consumption, CO2 Emissions and Cost of Existing Urban Residential Buildings in Hangzhou City, China

Abstract: China has become the second largest emitter of CO 2 in the world. As one of the largest energy consumers, urban residential buildings are required to reduce energy consumption. However nearly all existing urban residential buildings in the Hot Summer and Cold Winter Region of China were built with poor thermal quality. Increasing a building's energy performance has proven to be very helpful in alleviating the pressure of energy shortages and in reducing CO 2 emissions. After analyzing the climate of the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The proposed framework could potentially be applied to large-scale projects, such as campus district renovation or neighborhood renovation. Studying the energy consumption reduction on a large scale is a relatively new focus area: the first published study on energy retrofit on the district level was found in 2008 by [58]. Since then, several large-scale studies have been published, such as Moscow's residential district renovation impact on energy and emissions [59].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed framework could potentially be applied to large-scale projects, such as campus district renovation or neighborhood renovation. Studying the energy consumption reduction on a large scale is a relatively new focus area: the first published study on energy retrofit on the district level was found in 2008 by [58]. Since then, several large-scale studies have been published, such as Moscow's residential district renovation impact on energy and emissions [59].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic literature review focuses on the residential con tion sector and contains 52 single-family (SF) buildings, 22 multi-family (MF) buil and one zero-energy residential living laboratory (LL) case study building (Figure A Most of the analysed case studies (43) are based on existing building stock, wh others (32) are based on the assessment of GHG emissions of newly built or designe idential buildings. Based on the collected case studies, it seems that there is a lack is apparent and urgent in both developing and developed economies [93].…”
Section: Appendix a List Of Case Studies And Basic Propertiesmentioning
confidence: 99%
“…In this paper, the relative values of the energy-saving effects in fact are assumed to be the same as those in the thermal simulation, as shown as equation (1).…”
Section: Revision Process 41 Revision Of Energy Saving Effectsmentioning
confidence: 99%
“…reveals that: (1). The absolute values of the energy saving effects of the plans in the thermal simulation are highly exaggerated, due to the great discrepancy between the heating and cooling loads in the thermal simulation and in authentic situation, though the relative values of the actual energy saving effects are assumed to be the same as those in the thermal simulation.…”
Section: Revision Process 41 Revision Of Energy Saving Effectsmentioning
confidence: 99%
See 1 more Smart Citation